Analisis Keberlanjutan Program Padi Organik di Desa Pereng Kecamatan Mojogedang Kabupaten Karanganyar (Studi Kasus Kelompok Tani Rukun Makaryo) - Permatasari, Putri; Winarno, Joko; Anantanyu, Sapja; Wibowo, Agung; Suwarto, Suwarto; Suryono, Suryono (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
One way to realize a sustainable agricultural system is with an organic farming system. Rukun Makaryo Farmer Group is the farmer group in Karanganyar Regency that referred to organic farming system training at the National level from 2007-2011. Rukun Makaryo Farmer Group has succeeded in creating castle waste as fermented solid and liquid organic fertilizer. Rukun Makaryo Farmer Group has the opportunity to be assessed by the organic rice certification team from the Persada Organic Rice Certification Agency on members 5,9 hectares of land. This research aims to analyze the sustainability of the organic rice program in Rukun Makaryo Farmer Group; 1) Analyze the obstacles that hinder the process of sustainability of the organic rice program, 2) Analyze the hopes of the farmers in realizing of sustainability organic rice program, and 3) Formulate alternative recommendations strategies for assisting farmer groups so that in the future they can carry out the sustainability of the organic rice program independently. This research was conducted in Pereng Village, Mojogedang, Karanganyar, with seventeen respondents of organic farmers. This research method was a qualitative description with a phenomenological approach. This research activity will be gained experience and subjective awareness and interpretation of efforts to maintain the status of organic rice certification. The results showed that; 1) Obstacles that hinder the process of sustainability of the organic rice program are low education, age of farmers, high cost of certification, difficulties in marketing, and complexity of the cultivation technique process, 2) Rukun Makaryo Farmer Group hopes that to have access marketing partnerships so that there will be an increase in selling prices and the development of economic conditions for farmers, and 3) Recommendations for assistance by rice field approach, simultaneous planting system, strengthening farmer organizations with establishing the Internal Control System (ICS), and developing agricultural products marketing systems and facilities.